Immunotherapy of chronic myeloid leukemia: present state and future prospects - Vonka, Vladimír (Immunotherapy, 2010)
In spite of the considerable successes that have been achieved in the treatment of chronic myeloid leukemia (CML), cure for the disease can only be obtained by the present means in a rather small minority of patients. During the past decade, considerable progress has been made in the understanding of the immunology of CML, which has raised hopes that this disease may be curable by supplementing the current targeted chemotherapy with immunotherapeutic approaches. More than ten small-scale clinical trials have been carried out with experimental vaccines predominantly based on the p210bcr-abl fusion protein. Their results suggested beneficial effects in some patients. Recent data obtained in human patients as well as in animal models indicate that the p210bcr-abl protein does not carry the immunodominant epitope(s). These observations, combined with the recognition of an ever increasing number of other immunogenic proteins in CML cells, strongly support the concept that gene-modified, cell-based vaccines containing the full spectrum of tumor antigens might be the most effective immunotherapeutic approach. Recently created mathematical models have provided important leads for the timing of the combination of targeted drug therapy with vaccine administration. A strategy of how targeted drug therapy might be combined with vaccination is outlined.
Keywords: chronická myeloidní leukemie; Forecasting; Cancer Vaccines; experimentální leukemie; Humans; Antigens, Neoplasm; Immunodominant Epitopes; Antineoplastic Agents; Mice; zvířata; očkovací schéma; Combined Modality Therapy; bcr-abl fúzní proteiny; aktivní imunoterapie; Clinical Trials as Topic; Models, Immunological; protinádorové látky; klinické zkoušky jako téma; Immunization Schedule; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Immunotherapy, Active; imunodominantní epitopy; modely imunologické; předpověď; protinádorové vakcíny; kombinovaná terapie; antigeny nádorové; imunoterapie; myši; Fusion Proteins, bcr-abl; transformované buněčné linie; Animals; lidé; Vaccination; Leukemia, Experimental; Cell Line, Transformed; vakcinace; Immunotherapy